Removable partial dentures: eliminating retainers in the anterior zone - Christian Eugenio Rochefort-Quiroz; Constanza González; Danilo Ocaranza; Diego Andrés Muñoz-Rivera (Universidad de Antioquia, 2020)
Introduction: one of the main factors for discomfort in users of removable partial prosthesis is the presence of visible retainers in the anterior zone. In Kennedy Class III arches, that is, exclusively dental loading channels (in which the functional forces reach their final receptor: the alveolar bone), anterior zone retainers may be eliminated by selecting an appropriate prosthetic insertion and removal axis, and mainly by carving guiding planes that should provide retention by mechanical rubbing. This is an in vitro experimental study aimed at proving the hypothesis that it is possible to obtain functional retention in a removable partial prosthesis of dental loading channel without using retainers in the anterior zone. Methods: 7 maxillary models with different types of toothless process were used. As a common characteristic, they all were classified as Kennedy Class III with partial denture arches. A Cr-Co metallic base was built for each model according to their clinical situation. Their design allowed them to be exposed to traction in a universal traction machine (Tinius Olsen H5K-S). Results: the proposed hypothesis was confirmed as expected. The traction force needed to displace the metallic bases with retainers in the anterior zone was 16.93 Newton in average. On the other hand, the metallic bases without retainers in the anterior zone showed an average of 12.84 N. The average values obtained for both groups are higher than those reported in the literature (4.903 N). Conclusions: in Class III removable partial dentures it is possible to use metallic bases with no retainers in the anterior zone.